(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Hepatitis is inflammation of liver parenchyma mostly caused by viruses and other factors. It’s a non-specific prodromal illness characterized by headache, myalgia, arthralgia, nausea, anorexia, dark urine, yellow discoloration of skin, mucosa, sclera and other tissues etc. Methodology: A diagnosed case of hepatitis, 37yrs old female patient, admitted in at Government Ayurvedic college & Hospital, Kadam Kaun, Patna, Having IPD No.1006, RN.7178. Based on symptoms, supported by blood investigation reports and Ayurvedic parameters, the condition diagnosed as Yakritsotha. Oral medicines given: Aryogyavardhini Vati, Punarnava Mandur, Shallaki, Syp. Kalmegh, Kasis Bhasm, Liv 52 HB, Phaltrikadi Kwatha, cap. Stresscom along with Pathya apathya ahara vihara were prescribed. Result: There was drastic decrease in all the symptoms. The effect of treatment was monitored during the follow up with routine blood examinations. The bilirubin level decreased from initial 6.2mg/dl to 1.0mg/dl. Discussion: This article is a discussion about a case of Hepatitis which was successfully treated by Ayurvedic line of treatment. The signs and symptoms, causes, pathos-physiology of Hepatitis, along with its co-relation in Ayurveda as Yakritsotha, its line of treatment and possible the mode of action of drugs were the main points of consideration. Conclusion: Use of medicines such as Aryogyavardhini Vati, Punarnava Mandur, Shallaki, Syp. Kalmegh, Kasis Bhasm, Liv 52 HB, Phaltrikadi Kwatha, cap. Stresscom along with Pathya apathy ahara vihara showed good result without any complication in the present study.